Road Pavement Information Modeling through Maintenance Scenario Evaluation. (24th May 2021) - Oreto, C.; Biancardo, S. A.; Viscione, N.; Veropalumbo, R.; Russo, F.
Abstract : Road maintenance operations involve the preservation of the optimal functionality of the pavement. Sometimes the rehabilitation of the pavement layout does not have long lasting effects due to a lack of compliance with the constraints imposed by the technical specifications for the design of materials. The purpose of this paper is to present an efficient BIM tool to help in road maintenance operations through the management of data arising from laboratory testing of road pavement bituminous materials required for the quality control of mixtures. The database associated to the BIM model is a collection of three years of data derived from laboratory investigation on bituminous mixtures' samples adopted for the maintenance of four main roads located in southern Italy. An algorithm that interacts with the three-dimensional road model has been implemented in order to give road administrations an easy-to-read alert signal for the road pavement structure of the road network that may present the most critical conditions due to poor mechanical and physical features.